Thermoregulatory effects of guava leaf extract-menthol toner application for post-exercise use - Titeyut Wongsanao; Wipavadee Leemingsawat; Vipaporn Panapisal; Thanomwong Kritpet (Taylor & Francis Group, 2021)
Context Psidium guajava L. (Myrtaceae) leaf contains a wide variety of bioactive compounds that contribute valuable effects on human well-being. Objective This study investigates the influence of guava leaf extract-menthol toner on thermoregulation, including perspiration, skin temperature, and recovery heart rate. Materials and methods This randomised, placebo-controlled clinical trial assessed the effects of the guava leaf extract-menthol toner and placebo with a 1-week washout period. Sixty-four participants were enrolled. The participants exercised on a treadmill until a 75% heart rate reserve was achieved for 5 min, followed by a 5 min post-exercise rest period. The skin temperature and heart rate were then measured before 5 mL of the testing product was sprayed to specific areas of the body, left it for 30 sec before wiped off. Post-exercise perspiration and skin temperatures were collected by sweat patches and measured by the Skin-thermometer ST500, respectively. A 20 min heart rate monitoring period started 10 min after the exercise and measured every 2 min intervals. Results Use of the toner significantly reduced post-exercise perspiration to approximately half of the baseline and placebo use values (p < 0.05). Furthermore, relative heart rate changes showed no significant differences among the tests (p > 0.05). Skin temperature was also unaffected (p > 0.05). Discussion and Conclusion Guava leaf extract-menthol toner reduced perspiration by astringent effects but did not influence heat dissipation and did not affect cardiovascular mechanism compared to the controls. Additional cleaning with guava leaf extract-menthol toner could offer better hygiene after a workout.